2019
DOI: 10.29333/iji.2019.12216a
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Students’ Perception on Learning by Questioning Scale in Physics

Abstract: The aim of the study was describing the development and validation of students' perception on learning by questioning (LBQ) scale in physics. Research and Development (R & D) design was utilized in the research method. The number of senior high school students involved in the research were 224 students, composed of 95 boys (42.41%) and 129 girls (57.59%) from Indonesia. The instrument used for this study was the questionnaire of students' perception on LBQ. Analysis of data used SPSS 21 and AMOS 21, which cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It is noted that this study is fixed in the earlier empirical studies only. This study is also supported by the author's experiences in dealing with developing scale studies through survey research (see Suprapto et al 2017;Suprapto, 2019a;and Suprapto, 2019b). To sum up, this study was focused on the following research questions.…”
Section: Problem Of Studymentioning
confidence: 68%
See 1 more Smart Citation
“…It is noted that this study is fixed in the earlier empirical studies only. This study is also supported by the author's experiences in dealing with developing scale studies through survey research (see Suprapto et al 2017;Suprapto, 2019a;and Suprapto, 2019b). To sum up, this study was focused on the following research questions.…”
Section: Problem Of Studymentioning
confidence: 68%
“…This number is considered as the minimum number in survey study (Suprapto et al, 2017;Suprapto, 2019a). Additionally, the proportion between the number of item scale and participants should be at least 1:10 (Lin et al 2015b;Suprapto, 2019b;Uzuntiryaki & Aydin, 2008). For example, if the number of items is 20 then the minimum of participant should be 200 respondents.…”
Section: Searching Criteriamentioning
confidence: 99%
“…From the results of data processing shown in Table 3, it is obtained Bartlett's Test of Sphericity with Chi-Square value of 2363.817 (df 45) and the sig = 0.000 <0.05. The calculated KMO value is 0.845, and the pvalue is 0.000 (<0.05), according to [Suprapto, 2019a;2019b;Widarjono, 2010], the KMO and Bartlett's test values obtained have the criteria of "useful". Furthermore, according to Wachidy & Supardiyono (2018), the value of KMO and Bartlett's test for the correlation between the desired variables is > 0.50, and the significance of the study is 0.05.…”
Section: Fun Tech Zonementioning
confidence: 98%
“…The five senses, which are held in high regard, can be used to gather information about someone through perception. (Suprapto, 2019) The intended meaning of the means stimuli is why they were chosen. Positive and negative impressions are frequently distinguished in the study of perception.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis's findings revealed that the lecturer primarily initiated the pattern of interaction, with the distribution of data class being the primary pattern to occur. The fifth analysis was produced by Semi (Suprapto, 2019), This thesis is a descriptive qualitative study on how participants interacted in the lecturer and student conversation in the classroom. The study's findings indicate that the instructor was more engaged in the conversation.…”
Section: Introductionmentioning
confidence: 99%